“AN APPLIED RESEARCH TO SUPPLY ENERGY COMING FROM EXPLOITATION OF BIOMASS SCRAPS TO “LITTLE AND MIDDLE ENTERPRISE (LME)” (PART ONE) - Patania, Francesco; Gagliano, Antonio; Nocera, Francesco; Antonio, Agrifoglio (European Scientific Journal, ESJ, 2015)
The research was funded by “Operative National Plan - European Capital for Regional Development” (PON-FERS 2007-2013, Industry 2015). Authors considered the Sicilian LME producing wastes from operational processes as like woody chips, wood shavings, shells of hazelnut or almond and so on. A previous survey carried out on a consistent sample of Sicilian LME showed that electrical power required by operational processes ranges substantially around three main values (250, 500 and 635 kWe) and research was addressed to obtain previous values of electrical power. People takes in consideration the exploitation of biomass through pyrolysis process since it produces syngas usable as fuel in gas-turbine of CHP plant, bio-oil and biochar too, both of them able to supply thermal energy to many section of plant. The whole paper describes the general plane of research and guidelines for: • calculus of sizes of biomass stockpile storage (storage and drying - first section) • design of equipments of pyrolysis process and exhausts treatment (pyrolysis process – second section) • design of cogeneration system (CHP techniques – third section). The result of research specifies too the economical decreasing of operational costs of LME and the remarkable environmental benefits arose by exploitation of biomass. For room reason the part one of paper describes the generalized characteristics of research and results of calculations to design drying and storage section.